Emotional Intelligence, Optimism, and Peer Support as Predictors of Students’ Psychological Well-Being: A Case Study to Enhance Educational Management Quality - Fauzi Rochman; Raden Partino; Khoiruddin Bashori; Mohammad Syifa Amin Widigdo (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Background: The undergraduate thesis writing process is a critical phase that can adversely affect students’ psychological well-being. From an educational management standpoint, addressing this is crucial for student retention, success, and institutional quality. Methods: This quantitative study investigated the influence of emotional intelligence, optimism, and peer support on the psychological well-being of 233 thesis-writing students from two Indonesian universities. Data were collected using validated scales and analyzed using Structural Equation Modeling (SEM) in LISREL. Results: The findings revealed that the three variables simultaneously had a positive and significant effect on psychological well-being, accounting for 89% of its variance (R² = 0.89). Each construct also contributed a significant positive effect individually. Conclusion and Implications: The results underscore the necessity for a proactive educational management approach. Higher education institutions are advised to move beyond a purely academic focus and develop comprehensive support systems. These systems should integrate structured training for emotional skills, programs to foster optimism, and university-facilitated peer support networks. Incorporating these elements into the core student affairs strategy is essential for creating a healthier learning environment and promoting sustainable academic success. This study is among the first to integrate emotional intelligence, optimism, and peer support within a single SEM-based model in the thesis-writing context, advancing the educational management literature by identifying peer support as the dominant institutional leverage point for student psychological well-being.